“Sistem maklumat pengurusan khairat kematian” for Madrasah Hidayah Seksyen 11 in Shah Alam / Hamizah Megat Othman and Nurul Nadia Hassan - Megat Othman, Hamizah; Hassan, Nurul Nadia (2013)
This paper presents “Sistem Maklumat Pengurusan Khairat Kematiaan”, a web based application integrated with e-mail has been developed for the resolving some issues which involves in Badan Khairat Kematiaan (BKK) daily operational activities. This system main objective has been focused on membership of management information system and annual fee management. Furthermore, this system has been developed to replace the existing manual system to a fully automate web based system to ensure ease of management and time saving by the BKK’s administrators. Compared to the traditional manual system, the advantages of this system can be enjoyed by BKK’s members to register, check their status and view all their information. In addition, this system is different from other system in term of its user friendly interface, more automatically and also the technology that have been used. The centralized database concept that had been implemented in this system will ensure the data can be accessed easily by the validated users. Otherwise, this system allows the BKK’s administrators to send the email to BKK’s members about latest news information in easy way. This system used the Ruby language, Sqlite 3 database as the information storage and Ruby on Rails used as a MVC framework. This project hope can be a system for use and common good nowadays and future time.